Myrica rubra Extracts Protect the Liver from CCl4-Induced Damage. (14th February 2011) - Xu, Lizhi; Gao, Jing; Wang, Yucai; Yu, Wen; Zhao, Xiaoning; Yang, Xiaohe; Zhong, Zengtao; Qian, Zhong-Ming
Abstract : The relationship between the expression of mitochondrial voltage-dependent anion channels (VDACs) and the protective effects of Myrica rubra Sieb. Et Zucc fruit extract (MCE) against carbon tetrachloride (CCl4 )-induced liver damage was investigated. Pretreatment with 50 mg kg −1, 150 mg kg −1 or 450 mg kg −1 MCE significantly blocked the CCl4 -induced increase in both serum aspartate aminotransferase (sAST) and serum alanine aminotransferase (sALT) levels in mice ( P < .05 or .01 versus CCl4 group). Ultrastructural observations of decreased nuclear condensation, ameliorated mitochondrial fragmentation of the cristae and less lipid deposition by an electron microscope confirmed the hepatoprotection. The mitochondrial membrane potential dropped from −191.94 ± 8.84 mV to −132.06 ± 12.26 mV ( P < .01) after the mice had been treated with CCl4 . MCE attenuated CCl4 -induced mitochondrial membrane potential dissipation in a dose-dependent manner. At a dose of 150 or 450 mg kg −1 of MCE, the mitochondrial membrane potentials were restored ( P < .05). Pretreatment with MCE also prevented the elevation of intra-mitochondrial free calcium as observed in the liver of the CCl4 -insulted mice ( P < .01 versus CCl4 group). In addition, MCE treatment (50–450 mg kg −1 ) significantly increased both transcription and translation of VDAC inhibited by CCl4 . The above data suggest that MCE mitigates the damage to liver mitochondria induced by CCl4, possibly through the regulation of mitochondrial VDAC, one of the most important proteins in the mitochondrial outer membrane.